Genotype × environment interactions and yield stability of common bean (Phaseolus vulgaris) genotypes in different altitudes - FAIRUZ LUTHFI HANIFAH; DARMAWAN SAPTADI; KUSWANTO KUSWANTO; NIKEN KENDARINI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Hanifah FL, Saptadi D, Kendarini N, Kuswanto. 2026. Genotype × environment interactions and yield stability of common bean (Phaseolus vulgaris) genotypes in different altitudes. Biodiversitas 27 (5): d270515. https://doi.org/10.13057/biodiv/d270515. Common bean (Phaseolus vulgaris) is an important vegetable crop widely cultivated for its high nutritional and economic value, but its productivity is often affected by environmental variability. This research aimed to evaluate genotype × environment interactions, adaptability, and stability of four bush-type common bean genotypes and two check varieties in two agroecological zones, specifically high-altitude area and medium-altitude area. This research was arranged in a randomized block design with four replications per location. Nine parameters were observed, including plant height, number of leaves, days to flowering, days to harvest, number of pods per plant, pod length, pod diameter, pod weight per plant, and yield. A combined analysis of variance revealed significant effects of genotype, environment, and G × E interactions on most traits. Stability analysis was performed using parametric and nonparametric methods. GGE biplot analysis was applied to visualize genotype performance and stability simultaneously. The results indicate that genotypes AB (14.07 t ha-1) and AK (14.19 t ha-1) have the highest yields and broad adaptability, owing to their low contributions to G × E interactions, making them relatively stable at both medium and high altitudes. Genotype BK (12.82 t ha-1) has high yields only in the high altitudes, indicating specific adaptability to high altitude conditions. These findings highlight AB and AK as promising candidates for broad adaptability in high and medium altitude areas, and BK for targeted application in highland production areas.